Optimasi Gliserin dan Propilen Glikol dalam Sediaan Antioksidan Essence Ekstrak Kayu Secang (Caesalpinia sappan L.) - Ameliana, Lidya; Winarti, Lina; Roja, Talidah Alqibtiyah (Journal of Agropharmacy, 2024)
Facial skin problems are often caused by skin frequently exposed to free radicals, causing damage to skin cells. Usually, skin damage is characterized by a non-smooth skin structure, the appearance of dark spots, wrinkled skin, and dull skin. Antioxidants are one of the compounds that can protect cells from the influence of free radicals and slow down or prevent the oxidation process. To help reduce, stop, and slow down the adverse effects of free radical exposure, antioxidant essence preparations are used. In this study, glycerin and propylene glycol have been optimized in the preparation of sappan wood extract essence as an antioxidant. The purpose of this study is to determine the optimum concentration of glycerin and propylene glycol as a humectant in the essence preparation of sappan wood extract. In this study, the evaluation carried out includes pH tests, viscosity, and IC 50 antioxidant activity. In this study, essence characterization tests were also carried out including organoleptics, homogeneity, and dispersibility. From the results of the pH test, it was found that all essence formulas had a pH in the range of 5.5-6.0; viscosity in the range of 1.0-2.0 dPa.s; and IC50 test of antioxidant activity in the range of 100-125 μg/mL. The optimum essence formula has a propylene glycol concentration of 10% with a desirability of 0.871, with a predicted pH value of 5.658, a viscosity value of 1.256 dPa.s, and an IC50 value of 106.473 (μg/mL).